Cross sectional and longitudinal study on selenium, glutathione peroxidase, smoking, and occupational exposure in coal miners. Issue 4 (1st April 2001) - Nadif, R; Oryszczyn, M-P; Fradier-Dusch, M; Hellier, G; Bertrand, J-P; Pham, Q-T; Kauffmann, F
Abstract : OBJECTIVES: To understand the variations of selenium (Se) concentration relative to changes in occupational exposure to coal dust, taking into account age and changes in smoking habits in miners surveyed twice, in 1990 and 1994. To better understand the relation of Se concentration with glutathione peroxidase activities (GSH-Px) in these miners. METHODS: In 1994, blood samples were obtained from active (n=131) and retired (n=40) miners without coal worker's pneumoconiosis, in whom Se concentration was available at both surveys and in whom International Labour Organisation (ILO) profusion grade had not been changed. Active miners were exposed to high dust concentrations (n=48) or low dust concentrations (n=83). Miners were classified into three subgroups according to their estimated cumulative exposure to dust, and into three subgroups according to their smoking habits. RESULTS: Selenium concentration and GSH-Px activities were significantly lower in active than in retired miners (Se adjusted means: 62.6 v 72.2 ng/ml p=0.01). Moreover, Se concentration was lower in miners exposed to high compared with those exposed to low dust concentrations (adjusted means: 59.4 v 65.8). In miners exposed to high dust concentrations, Se concentration was significantly lower whereas erythrocyte GSH-Px activity was significantly higher in the subgroup with estimated cumulative exposure >68 mg/m 3 .y. In all miners, plasma GSH-Px activity was correlated with Se concentration ( r =0.22, p<0.005). The 4 year Se changes were negatively related to exposure to high dust concentrations and positively related to change in exposure from high to retirement and to change from smoker to ex-smoker (p=0.01). CONCLUSION: The variations of Se concentration in relation to changes in occupational exposure to coal dust and in smoking habits, and the close correlation found between plasma Se concentration and GSH-Px activity suggest that both are required in antioxidant defence. These results agree well with the hypothesis that the decrease in Se concentration reflects its use against reactive oxygen species generated by exposure to coal mine dust and by smoking.